2021
DOI: 10.3390/vaccines9070781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Hospitalized COVID-19 Patients Who Received at Least One Dose of COVID-19 Vaccine

Abstract: The clinical trials of the COVID-19 vaccines that are authorized in the European Union have revealed high efficacy in preventing symptomatic infections. However, during vaccination campaigns, some vaccine recipients, including those partially and fully vaccinated, will experience severe COVID-19, requiring hospitalization. This may particularly concern patients with a diminished immune response to the vaccine, as well as non-responders. This work has retrospectively analyzed the 92 cases of patients who were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 39 publications
4
42
1
Order By: Relevance
“…The short-term results of clinical trials of different COVID-19 vaccines demonstrated their high efficacy against symptomatic SARS-CoV-2 infection [4][5][6], later confirmed by the first post-authorization, real-world observations [8]. However, accumulating evidence suggests that this efficacy gradually decreases due to two main factors: (i) a decline in serum anti-spike IgG antibody levels that occurs within a few months following the last vaccination [9,10], and (ii) the emergence of novel SARS-CoV-2 variants, classified as variants of interest (VOIs) and variants of concern (VOCs), such as B.1.617.2 (delta variant), that reveal higher transmissibility and can lead to higher viral loads in the upper respiratory airways [11,12].…”
Section: Introductionmentioning
confidence: 81%
“…The short-term results of clinical trials of different COVID-19 vaccines demonstrated their high efficacy against symptomatic SARS-CoV-2 infection [4][5][6], later confirmed by the first post-authorization, real-world observations [8]. However, accumulating evidence suggests that this efficacy gradually decreases due to two main factors: (i) a decline in serum anti-spike IgG antibody levels that occurs within a few months following the last vaccination [9,10], and (ii) the emergence of novel SARS-CoV-2 variants, classified as variants of interest (VOIs) and variants of concern (VOCs), such as B.1.617.2 (delta variant), that reveal higher transmissibility and can lead to higher viral loads in the upper respiratory airways [11,12].…”
Section: Introductionmentioning
confidence: 81%
“…Although the risk of breakthrough infections may increase over time in vaccinated individuals due to the waning of serum antibody levels and can be further elevated due to circulation of some more transmissible SARS-CoV-2 variants (e.g., B.1.617.2), this does not equal an increased risk of breakthrough diseases, especially ones leading to hospitalization or risk of death. Data originating from different parts of the world consistently show that COVID-19 vaccines retain high levels of protection against severe infections and death; that is, the risk of hospitalization and death due to severe COVID-19 is significantly higher in unvaccinated individuals, although its exact values may vary across populations due to different settings and types of administered vaccines [44][45][46][47][48][49][50][51][52]. For example, data collected by the US Centers for Disease Control and Prevention indicate that, in August 2021, unvaccinated individuals had a 6-fold higher risk of SARS-CoV-2 infection and an 11-fold higher risk of dying from COVID-19 [53].…”
Section: Protection Against Severe Disease After the Initial Vaccination Regime Remain Highmentioning
confidence: 98%
“…The production of specific antibodies starts a few weeks after the first dose, but a second dose is required for optimal protection against COVID-19 [6][7][8]. As recently shown among those hospitalized due to COVID-19 in the first half of 2021, infections among vaccinated people are sporadic [9]. Recent studies suggest that humoral immunity against SARS-CoV-2, associated with natural infection or vaccination, may persist for more than six months, but specific antibody levels decline over time [7].…”
Section: Introductionmentioning
confidence: 99%